Training regulations and how they come about - Lorig, Barbara [Herausgeber]; Stöhr, Andreas [Herausgeber]; Schwarz, Henrik [Herausgeber] (Bundesinstitut für Berufsbildung, 2017)
"The German government uses laws and regulations to regulate the legal framework for vocational training in the 'dual' vocational training system (which combines part-time vocational schooling with practical work experience). Training regulations are legal provisions that outline the aims and content of and examination requirements for in-company training. The Federal Institute for Vocational Education and Training prepares the content of training regulations for the government. It develops drafts together with on-the-ground experts from the actual vocational training field who have been delegated by management and labour. This brochure contains information about the process involved in developing training regulations and offers an overview of materials and aids that BIBB can provide for implementing training regulations in day-to-day practice." (Editor, BIBB-Doku)
Dt. Ausg. u.d.T.: Ausbildungsordnungen und wie sie entstehen
Keywords: S 2.2.1 Ordnung von Ausbildungsberufen; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Neuordnung der Ausbildungsberufe; Ausbildungsordnung; Verfahren